Promoting independent ambulation: A case study of an elementary school student with developmental disabilities. (September 2016) - O'Handley, Roderick D.; Dadakhodjaeva, Komila; Radley, Keith C.; Dart, Evan H.
Highlights: A child with developmental disabilities and ambulatory deficits was included in the study. Intervention was conducted in a school setting. The child was taught to use his walker device using a forward chaining procedure. The child was also taught to increase his total distance walked. Results were maintained at two months post intervention. Abstract: The limited independent ambulation of individuals with developmental disabilities may be improved with the utilization of support walker devices. In the present study, a forward chaining procedure with an embedded changing criterion component was used to teach an elementary school student with multiple disabilities to acquire and maintain the skills needed to use his walker device successfully, and to increase his total distance walked while using his walker device. Results indicated that the student quickly acquired three of the four requisite steps necessary to use the walker device, but eventually acquired all four steps after procedural modifications. After mastering the four steps, the student gradually increased his total distance walked. Results were maintained when assessed two months post-intervention. Limitations and directions for future research are discussed.